The Measurement of Pancasila : An Effort to Make Psychological Measurement of Pancasila Values - Eko Aditiya Meinarno (Fakultas Psikologi Universitas Pancasila, 2011)
Pancasila is a national point of view and way life of the Indonesian people, set up by the founding fathers and promulgated as philosophical foundation of the Indonesian state. As a way of life, Pancasila is very indigenous. Today, Pancasila is more often studied as political construction and citizenship. Therefore, the authors develop this scale, which can serve as a tool for researcher, especially in social and political psychology area in Indonesia. This scale can also contribute in obtaining overview of Pancasila in the society and can serve as a reference to public decision maker, especially in developing national identity. The development of this measurement is based on values contained in the five principles of Pancasila. The trial is conducted to 41 students from faculty of psychology. For data collection, QuestionPro is used as online survey software. In terms of the analyzed item, the initial scale consists of 37 items, and then is reduced to 32 items. The reliability coefficient using Cronbach's Alpha is 0.848. One of item, namely item no.30, has the highest correlation coefficient. Overall, we find highly corrected item-total correlation in the five principles of Pancasila. This result has linearity from Meinarno's (2010) finding in folklore values. The five principles of Pancasila frequently appears in the Sumatran and Javanese folklores.